Pharmacodynamic Model of the Hemodynamic Effects of Propofol and Remifentanil and Their Interaction with Noxious Stimulation - Maite Garraza-Obaldia; Sebastian Jaramillo; Zinnia P. Parra-Guillen; José F. Valencia; Pedro L. Gambús; Iñaki F. Trocóniz (Pharmaceutics)
Background: Despite the known impact of propofol and remifentanil on hemodynamics and patient outcomes, there is a lack of comprehensive quantitative analysis, particularly in surgical settings, considering the influence of noxious stimuli. The aim of this study was to develop a quantitative semi-mechanistic population model that characterized the time course changes in mean arterial pressure (MAP) and heart rate (HR) due to the effects of propofol, remifentanil, and different types of noxious stimulation related to the clinical routine. Methods: Data from a prospective study were used; the study analyzed the effects of propofol and remifentanil general anesthesia on female patients in physical status of I-II according to the American Society of Anesthesiologists (ASA I-II) undergoing gynecology surgery. Patients were consecutively assigned to different administration schemes of propofol and remifentanil targeted at different effect-site concentrations. Esophageal instrumentation, laryngeal mask airway insertion, hysteroscopy, and tetanus stimuli were applied. Data from patients with chronic hypertension were discarded. Results: MAP and HR observations from 77 patients were analyzed. The hemodynamic effects were described using turn-over models incorporating feedback mechanisms. Analyses revealed that propofol and remifentanil elicited effects on the turn-over of MAP and HR, respectively, with estimates of plasma drug concentrations causing an inhibition-half of the maximum effect (C50) of 8.79 µg∙mL−1 and 4.57 ng∙mL−1. Hysteroscopy exerted an increase in MAP (but not in HR), which was well-characterized by the model, with a predicted typical increase of 28 mmHg and a dissipation half-life of 33 min. The impact of other noxious stimuli on MAP or HR could not be identified. Model simulations indicated that propofol and remifentanil, titrated to inhibit the motor response to noxious stimuli, regardless of dose combinations, cause a significant risk of hypotension, especially following induction and at the end of surgery (when surgical intervention is completed, before the awakening phase). Conclusions: The developed semi-mechanistic and fully identifiable model provides quantitative information on how propofol, remifentanil, and surgical stimulus (hysteroscopy) interact to produce the hemodynamic changes (of MAP and HR) commonly observed in clinical practice.